NADPH Oxidase 3 Deficiency Protects From Noise-Induced Sensorineural Hearing Loss - Rousset, Francis; Nacher-Soler, German; Kokje, Vivianne Beatrix Christina; Sgroi, Stéphanie; Coelho, Marta; Krause, Karl-Heinz; Senn, Pascal (Frontiers in Cell and Developmental Biology, 2022)
The reactive oxygen species (ROS)-generating NADPH oxidase NOX3 isoform is highly and specifically expressed in the inner ear. NOX3 is needed for normal vestibular development but NOX-derived ROS have also been implicated in the pathophysiology of sensorineural hearing loss. The role of NOX-derived ROS in noise-induced hearing loss, however, remains unclear and was addressed with the present study. Two different mouse strains deficient in NOX3 or its critical subunit p22phox were subjected a single noise exposure of 2 hours using an 8-16 kHz band noise at an intensity of 116-120 decibel sound pressure level. In the hours following noise exposure, there was a significant increase in cochlear mRNA expression of NOX3 in wild type animals. By using RNAscope in situ hybridization, NOX3 expression was primarily found in the Rosenthal canal area, colocalizing with auditory neurons. One day after the noise trauma, we observed a high frequency hearing loss in both knock-out mice, as well as their wild type littermates. At day seven after noise trauma however, NOX3 and p22phox knockout mice showed a significantly improved hearing recovery and a marked preservation of neurosensory cochlear structures compared to their wild type littermates. Based on these findings, an active role of NOX3 in the pathophysiology of noise-induced hearing loss can be demonstrated, in line with recent evidence obtained in other forms of acquired hearing loss. The present data demonstrates that the absence of functional NOX3 enhances the hearing recovery phase following noise trauma. This opens an interesting clinical window for pharmacological or molecular intervention aiming at post prevention of noise-induced hearing loss.